The Feeling is Real: Emotion Elicitation in Virtual Reality. (November 2019) - Susindar, Sahinya; Sadeghi, Mahnoosh; Huntington, Lea; Singer, Andrew; Ferris, Thomas K.
Classical methods for eliciting emotional responses, including the use of emotionally-charged pictures and films, have been used to study the influence of affective states on human decision-making and other cognitive processes. Advanced multisensory display systems, such as Virtual Reality (VR) headsets, offer a degree of immersion that may support more reliable elicitation of emotional experiences than less-immersive displays, and can provide a powerful yet relatively safe platform for inducing negative emotions such as fear and anger. However, it is not well understood how the presentation medium influences the degree to which emotions are elicited. In this study, emotionally-charged stimuli were introduced via two display configurations – on a desktop computer and on a VR system –and were evaluated based on performance in a decision task. Results show that the use of VR can be a more effective method for emotion elicitation when study decision-making under the influence of emotions.